Surface and downhole recording of pseudorandom vibroseis sweeps - Dean, Timothy; Tulett, J.; Lane, D.; Puckett, M.; Vermeer, P.; MacDonald, S.; Iranpour, K. (2015)
© 2015 SEG.The use of pseudorandom sweeps has received periodic attention over the last 45 years. Previous testing has indicated that hydraulic vibrators may struggle to transmit such sweeps due to their rapid variation in instantaneous frequency and/or amplitude. In the test described here, we tested 12 sweeps at the surface and recorded 4 downhole. The results are encouraging, both in terms of the ability of hydraulic vibrators to transmit pseudorandom sweeps and for the energy to be received downhole. Unfortunately, the low-frequency performance of the sweeps is poor when compared to other low-frequency sweep design methods. The biggest drawback for these sweeps appears to be an inherent design flaw, in that their energy levels are too low and their sidelobe levels too high. If pseudorandom sweeps are to be used in future then clearly these issues must be addressed.